Cracks in the movement ; Justice served ; State of grace [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
The breaking away of the Metro Manila Rizal Committee from the Communist Party of the Philippines. The Committee accuses CCP leader Jose Maria Sison of dictatorship and inflexibility. The story of the investigation and trial of salvaging case in Benguet. A feature on "alternative music" singer-songwriter who use ethnic musical instruments in fusion with rock and pop.
Cracks in the movement (17 min.) -- Myrna Diones story (9 min.) -- State of grade (18 min.)
VHS
Keywords: Diones, Myrna -- Interviews; Nono, Grace -- Interviews; Alex Boncayao Brigade -- Interviews; Communist Party of the Philppines; Instrumental music -- Philippines; Murder victims -- Philippines -- Benguet; Police brutality -- Philippines